Adolescent Health Education in Don Bosco Frater Junior High School Students Tomohon City - Merdekawati Evangli Weken; Rakhmawati Agustina; Syafriani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Adolescents frequently encounter several nutrition-related issues, such as anemia, obesity, and chronic energy deficiency, among others. During the developmental phase of adolescence, individuals need guidance as well as encouragement from adult figures. There is a need for guidance in order to enhance individuals' self-awareness and awareness towards regularly arising concerns. Health education is an effective approach for enhancing individuals' understanding and abilities to transform their health-related behaviors through the process of acquiring knowledge. The purpose of this activity is to increase awareness of adolescent health education in Frater Don Bosco Junior High School . The methods this activity conducts interactive seminars and to assess the students' comprehension, the team conducts pre and post-tests utilizing the Web Tool platform to develop interactive quizzes. The result findings this activity can involve participants activaly and indicated a significant increase of 20.64% in participants' knowledge. The suggested recommendation for promoting enhanced understanding of adolescent health among students is to offer training programs to teachers and establish peer groups in schools.